Catalytically active gold clusters and nanoparticles for CO oxidation; Surface science; Vol. 601, iss. 18 - Pestryakov A. N. Aleksey Nikolaevich; Bogdanchikova N.; Simakov A.; Tuzovskaya I.; Jentoft F.; Farias M.; Diaz A. (2007, 2007)
ECOSS-24, Proceedings of the 24th European Conference on Surface Science